The results of use of myoplasty for closure of the pelvic floor defect after extralevator abdominoperineal excision of the rectum - N. A. Domansky; V. V. Semiglazov; A. M. Karachun; K. K. Lebedev; D. V. Samsonov; А. A. Domansky (Сибирский онкологический журнал, 2019)
Background. Extralevator abdominoperineal excision is associated with a high incidence of perineal wound complications. There is no uniform standard for choosing the method for pelvic floor reconstruction after extralevator abdominoperineal excision.The purpose of the study was to compare the results of extralevator abdominoperineal excisions of the rectum using various methods of perineal wound closure.Materials and Methods. Between 2014 and 2018, 120 patients underwent extralevator abdominoperineal excisions of the rectum using various options for closure of the pelvic floor. The patients were divided into 3 groups. Group I patients (n=64) underwent simple plasty of the peritoneal wound. Group II patients (n=43) underwent myoplasty using the gluteus maximus muscle. Group III patients (n=13) underwent myoplasty using the rectus abdominis muscle. The incidence of perineal wound complications in the early postoperative period was assessed.Results. The total number of perineal wound complications in Group I, II and III was 33 (51.5 %), 13 (30.2 %), and 6 (46.1 %), respectively. Grade IIIA-IIIB complications according to the Clavien-Dindo classification were observed in 25 % of Group I patients, in 18.6 % of Group II patients and in 7.7 % of Group II patients. Postoperative perineal wound complications occurred more often in Group I patients after simple plasty than in Group II and III patients after myoplasty (51.5 % versus 30.2 %). However, perineal wound complications were observed more often in Group III than in Group II (46.1 % versus 30.2 %, respectively). No significant differences in the frequency of complications between 3 groups were found.Conclusion. Using various options for closure of the pelvic floor after extralevator abdominoperineal excisions of the rectum, there was a tendency to reduction in the incidence of grade IIIA-IIIB perineal wound complications.